Baseline Characteristics of Mitochondrial DNA and Mutations Associated With Short-Term Posttreatment CD4+T-Cell Recovery in Chinese People With HIV - Liu, Anni; Wei, Qian; Lin, Haijiang; Ding, Yingying; Sun, Yan V.; Zhao, Dan; He, Jiayu; Ma, Zhonghui; Li, Feihu; Zhou, Sujuan; Chen, Xiaoxiao; Shen, Weiwei; et al. (Frontiers in Immunology, 2021)
Background: Mitochondrial DNA (mtDNA) profiles and contributions of mtDNA variants to CD4+T cell recovery in Euramerican people living with HIV (PLWH) may not be transferred to East-Asian PLWH, highlighting the need to consider more regional studies. We aimed to identify mtDNA characteristics and mutations that explain the variability of short-term CD4+T cell recovery in East-Asian PLWH. Method: 856 newly reported antiretroviral therapy (ART)-naïve Chinese PLWH from the Comparative HIV and Aging Research in Taizhou (CHART) cohort (Zhejiang Province, Eastern China) were enrolled. MtDNA was extracted from peripheral whole blood of those PLWH at HIV diagnosis, amplified, and sequenced using polymerase chain reaction and gene array. Characterization metrics such as mutational diversity and momentum were developed to delineate baseline mtDNA mutational patterns in ART-naïve PLWH. The associations between mtDNA genome-wide single nucleotide variants and CD4+T cell recovery after short-term (within ~48 weeks) ART in 724 PLWH were examined using Bootstrapping median regressions. Results: 74.18% and 25.82% of 856 participants were male and female. The median age was 37 years. 94.51% were of the major Han ethnicity. 69.04% and 28.62% were of the heterosexual and homosexual transmission. We identified 2352 types of mtDNA mutations and mtDNA regions D-loop, ND5, CYB, or RNR1 with highest mutational diversity or volume. Female PLWH rather than male PLWH at the baseline showed remarkable age-related uptrends of momentum and mutational diversity as well as correlations between CD4+T <200 (cells/μl) and age-related uptrends of mutational diversity in many mtDNA regions. After adjustments of important sociodemographic and clinical variables, m.1005T>C, m.1824T>C, m.3394T>C, m.4491G>A, m.7828A>G, m.9814T>C, m.10586G>A, m.12338T>C, m.13708G>A, and m.14308T>C (at the Bonferroni-corrected significance) were negatively associated with short-term CD4+T cell recovery whereas m.93A>G, m.15218A>G, and m.16399A>G were positively associated with short-term CD4+T cell recovery. Conclusion: Our baseline mtDNA characterization stresses the attention to East-Asian female PLWH at risk of CD4+T cell loss-related aging and noncommunicable chronic diseases. Further, mtDNA variants identified in regression analyses account for heterogeneity in short-term CD4+T cell recovery of East-Asian PLWH. These results may help individualize the East-Asian immune recovery strategies under complicated HIV management caused by CD4+T cell loss.